A Ni8 metallacalix[4]arene and a Cu4 molecular rhomboid: limiting the nuclearity of carboxysalen-like metal complexes. Issue 35 (2nd August 2016) - Fondo, Matilde; Doejo, Jesús; García-Deibe, Ana M.; Sanmartín-Matalobos, Jesús; Vicente, Ramón
Abstract : A Ni8 metallacalix[4]arene and a Cu4 molecular rhomboid can be obtained from a carboxysalen-like ligand with a flexible propylene spacer. Abstract : Octanuclear [Ni2 (L)(H2 O)2 ]4 ·7CH3 OH·12H2 O (1 ·7CH3 OH·12H2 O) and tetranuclear [Cu2 (HL)(CH3 OH)1.5 (H2 O)1.5 ]2 (ClO4 )2 ·2CH3 OH (2 ·2CH3 OH) (H4 L = 4-carboxysalpn or N, N ′-bis(4-carboxysalicylidene)-1, 3-propylenediamine) are obtained from similar reactions, the main difference coming from the slightly higher pH of the medium for the nickel reaction vessel. This small disparity of the pH leads to full deprotonation of the ligand in1 while one of the carboxylic functions remains protonated in2, making it unable to act as a donor and, therefore, justifying the different nuclearity of both compounds. In any case, the isolation of complexes of H4 L with limited nuclearity is remarkable, given that similar carboxysalen-based ligands lead to coordination polymers when the carboxylic functions are partially or fully deprotonated. This indicates that not only the pH of the medium but also the longer propylene spacer of the Schiff base have a fundamental role in the nuclearity of the isolated products.1 ·7CH3 OH·12H2 O is an odd Ni8 1, 3-alternate metallacalix[4]arene, formed from four symmetry-related [Ni2 (L)(H2 O)2 ] metalloligands, joined through the fully deprotonated carboxylic functions.2 ·2CH3 OH is a molecular rhomboid, built from two [Cu2 (HL)(CH3 OH)1.5 (H2 O)1.5 ] + metallotectons, linked through the only deprotonated carboxylic group of the ligand, the protonated carboxylic moiety remaining uncoordinated. In addition, the magnetic analysis of both polynuclear compounds shows that they are antiferromagnetic in nature and that the magnetic interaction between dinuclear metallotectons is negligible.